Impact of ICAR-DPR germplasm in Backyard poultry production - KUMAR, VIJAY; Rajkumar, U; Rao, S V Rama (Indian Farming, 2022)
Backyard poultry farming plays an important role in Indian economy. It contributes about 37.2% in Indian poultry population and 16.8% in egg production of the country. ICAR-Directorate of Poultry Research, Rajendranagar, Hyderabad, Telangana and their network research centers of AICRP on Poultry Breeding developed and released more than 10 chicken varieties to improve the productivity and income of backyard poultry farmers. Mostly, these varieties are used for dual purpose (meat and egg). In last 10 years (2010–20), a total of 387.07 lakh chickens were supplied to 3.72 lakh stakeholders in different parts of the country and annual mean contribution was estimated about `205.64 crore during the period which ranged from `162.45–277.06 crore/year.